Copyright as an Object of Banking Guarantee (Comparative Study of Indonesia and Singapore) - Rahmadani, Salsabillah Suci; Mahrunnisa, Desy Rizky; Maharani, Aliffia Intan; Aveyory, Immanuela Yvette (Fakultas Hukum, Universitas Diponegoro, 2021)
Copyright as an object of guarantee is stated in the 2014 UUHC No. 28 article 16 paragraph (3) that copyright can be used as an object of fiduciary guarantee. In practice, no bank has issued a regulation related to this. Through research with a statutory approach and comparing it with Singapore, the author finds that there are several gaps, where Singapore already has clear rules, specialized banks, valuation agencies and IP market agencies. Meanwhile, Indonesia is still constrained by the unpreparedness of banking institutions.Keywords: copyright, warranty, singapore, intellectual property rights.